Comparison of conventional ROTEM® cups and pins to the ROTEM® cup and pin mini measuring cells (MiniCup). (October 2015) - Haas, Thorsten; Spielmann, Nelly; Dillier, Claudia; Cushing, Melissa; Siegmund, Svenja; Krüger, Bernard
Abstract Background. Thromboelastometry (ROTEM®) is a well-established measurement to guide perioperative coagulation management. Recently, an enhancement for low volume specimens using cup and pin mini measuring cells (MiniCup) was invented for scientific non-clinical use. The MiniCup measuring cells allow testing with half of the blood volume required to run a test as compared to the conventional ROTEM® cup and pin (150 μL vs. 300 μL per assay). Objectives. The aim of this prospective study was to compare ROTEM® results using conventional cups and pins to the results of the MiniCup measuring cells. Methods. Blood samples drawn during major pediatric surgery were analyzed using the conventional ROTEM® and the MiniCup system to compare parameters from the EXTEM, INTEM and FIBTEM assays. Results. Citrated blood samples (n = 120) from 70 pediatric patients were analyzed. Results of the MiniCup cells were considerably different than the conventional ROTEM® cups and pins measurements. The MiniCup results show less clot firmness and demonstrate higher variability in the parameters reflecting the kinetics of clot building. Conclusion. The MiniCup measuring cells may offer advantages in pediatric care or research facilities, but specific reference ranges need to be established first, and adequate reproducibility must be determined by further studies before clinical use can be recommended.